Application of Coffee Skin-Based Green Packaging - A.Dian SryRezki; Arminas; Rianti Indah Lestari; Riskawati; Masbin Dahlan (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2021)
The concept of "Green" is evolving with new innovations and techniques to protect environmental sustainability, embodied by corporate social responsibility, green manufacturing, waste reduction, recycling and manufacturing of sustainable supply chains and environmentally friendly supply chains. To reduce the use of plastic packaging, the industrial world is turning to green packaging. The eco-friendly packaging that was the subject of the study was a cellulose-based polymer made from cellulose, a major component in plant tissue. Coffee pulp has a high hydrated cellulose microfibrils with a unique morphology using certain chemical treatments. The content of this cellulose can be used as environmentally friendly packaging paper that will be used as packaging of processed coffee products. The method used in this study is by chemical means to remove the lignin content on the coffee skin as well as mechanical methods in the manufacturing process. In this study conducted four (4) experimental scenarios to produce a strong coffee skin packaging and have smooth fiber. From the experiment it was obtained that the packaging with a coffee skin proportion of 33.33% and 66.67% used paper waste had the highest tensile strength with a maximum load that could be held 94.2183 N and a maximum length increase of 11.0262 mm due to finer and denser scrap paper waste fibers binding together to fill the gaps of used paper fibers that had hollowed out adhesive. This ratio also shows good resistance when made into coffee product packaging so that the packaging used becomes environmentally friendly packaging by utilizing coffee waste itself, to produce pulp from coffee skin which is further used as raw material for making coffee packaging.